Increasing Accessible Active Site Density of Non-Precious Metal Oxygen Reduction Reaction Catalysts through Ionic Liquid Modification - Zhang, Gui Rong; Yong, Cong; Shen, Liu Liu; Yu, Hui; Brunnengräber, Kai; Imhof, Timo; Mei, Donghai; Etzold, Bastian J.M. (ACS Applied Materials and Interfaces, 2023)
Non-precious metal catalysts show great promise to replace the state-of-the-art Pt-based catalysts for catalyzing the oxygen reduction reaction (ORR), while their catalytic activity still needs to be greatly improved before their broad-based application. Here, we report a facile approach to improving the performance of zeolitic imidazolate framework-derived carbon (ZDC) toward the ORR by incorporating a small amount of ionic liquid (IL). The IL would preferentially fill the micropores of ZDC and greatly enhance the utilization of the active sites within the micropores, which are initially not accessible due to insufficient surface wetting. It is also disclosed that the ORR activity in terms of kinetic current at 0.85 V depends on the loading amount of the IL, and the maximum activity is obtained at a mass ratio of IL to ZDC at 1.2. The optimum stems from the counterbalance between the enhanced utilization of the active sites within the micropores and the retarded diffusion of the reactants within the IL phase due to its high viscosity.
CRIS-Team Scopus Importer:2023-08-15
Keywords: electrochemically active surface area; ionic liquids; non-precious metal catalysts; oxygen reduction reaction; ZIF-derived carbon